Autonarrativas e modos de en-agir em educação, saúde mental e direito: experiência das famílias dos jovens participantes do Programa Oficinando em Rede de Mossoró - Oliveira Júnior, Vicente Celeste de (Universidade Federal Rural do Semi-Árido, 2015)
This research interacts directly with the theme of Inclusive Education, its core is the autonarrativa when you consider that the different worlds we produce occur in linguajear. It is a way to research that has taken relief in recent years. Observe with care to seek to apprehend the movements, actions that subjects coordinate in a production route constituted our research. The locus of our investigation was the Psychosocial Care Center for Children and Adolescents - CAPSi - Mossoro, a study that takes place in transdisciplinary perspective, situated in Multisdiciplinar field of Environmental Sciences, the problem consideraruma interacting with conservation a life of living things in the environment, the human being, be this who lives and suffers the consequences of what we are able to produce as linguajeando modes of existence. The cut we do is in autonarrativas produced by different subjects in an outreach program that takes place since 2010 in CAPSi of Mossoro. The subjects are Fellows Program and the coordinator to integrate the collective research and actions in language involving gestures, words, power devices and to know that shape the realities that we produce in the course of the experiment. A staff member of the research kindly gave us logbooks tissues in meetings with CAPSi the young family. The autonarrativa aims to build a text from the events experienced by the author, how has the viewer function of a journey lived by others, in short, is a construction of individuals narrated by its actions, omissions, ways of seeing , think, feel and act in itself. The autonarrativa methodology guided by the observation of the practice and followed by dialogue and theoretical reflection of the subjects' subjectivity is the way of life in the cognitive dimension of autopoietic beings, in the case of humans, weaving modes of existence linguajeando. Theorists who accompany us in our studies and scientific research, discuss, dialogue in this perspective and here we highlight: Humberto Maturana, Francisco Varela, Mário Osório Marques, Nize Pellanda, Claudia Freitas, Edgar Morin, Michel Foucault and Paulo Freire. The research is theoretical foundation ethics as a way of "en-act", an expression that reconstructed based on the concept of "enaction" developed by the brilliant scientist, biologist and philosopher, Francisco Varela, in his reflections on the - knowledge -. We understand that the families of narratives involve suffering, fighting, discouragement and sadness at the life they lead with their children with developmental disorder. They do not feel / live tracks where they can interact with changes, developments, to consider the dimensions of medical and educational action, which causes certain revolt. Mothers, grandparents, uncles or aunts, some parents, those who take concrete and even legal custody and education of young people express all the Love in care experience along the way. A single case that comes against the experience and processes of exclusion in Education were able to observe the mother's narratives of "H" when said that the school where your child studies have people who take care of him, which carry out activities aimed at him, that is joy. The survey results serve to distinguish a whole do necessary for the youth experience in Mossoro developmental disorder occurs in the context of care and knowledge, which implies effective and necessary actions in this field where they seek care and compromising Education institutions , Mental Health and Law in the region
Keywords: Jovens; Familiares; Educação; Saúde Mental; Direito; Youth; Family; Education; Mental Health; Law; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE